1996
DOI: 10.1111/j.1365-2591.1996.tb01377.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of the coronal leakage of two root canal sealers using an obligate anaerobe microbial marker

Abstract: The aim of this in vitro study was to investigate the coronal leakage of obligate anaerobes into root canals obturated with lateral condensation of cold gutta-percha with two root canal sealers. Sixty extracted human teeth with straight, single root canals were prepared using the modified double-flared technique with balanced force under copious irrigation until the master apical file was size 40. The teeth were divided randomly into experimental groups (40 teeth) and control groups (20 teeth). In the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…Whereas, Khayat et al 15 reported that the contamination of DTE exposed to saliva occurred in fewer than 30 days, a result that was partly similar to that obtained in the TEF group, which showed leakage in 50% of its samples in this time interval. The short period of contamination of this same group agreed with the data of the study of Chailertvanitkul et al 16 in which the time necessary for leakage with E. faecalis to occur ranged from 7 to 86 days. Bacterial tracers have been wisely used to provide data that are biologically and clinically more significant and relevant when compared with other methods.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas, Khayat et al 15 reported that the contamination of DTE exposed to saliva occurred in fewer than 30 days, a result that was partly similar to that obtained in the TEF group, which showed leakage in 50% of its samples in this time interval. The short period of contamination of this same group agreed with the data of the study of Chailertvanitkul et al 16 in which the time necessary for leakage with E. faecalis to occur ranged from 7 to 86 days. Bacterial tracers have been wisely used to provide data that are biologically and clinically more significant and relevant when compared with other methods.…”
Section: Discussionsupporting
confidence: 89%
“…In vitro studies have revealed that even with adequate root canal fillings and regardless of the obturation technique or filling material, leakage of bacteria (from saliva or in pure cultures) and bacterial products occurs along the root canal filling, even after a short-term challenge (12)(13)(14)(15)(16)(17)(18)(19). Findings from a cross-sectional study of 1010 root canal-treated teeth suggested that the quality of the coronal restoration had a greater impact on the periradicular status than the quality of the endodontic treatment (20).…”
mentioning
confidence: 99%
“…In 1996, Chailertvanitkul et al [18] investigated the coronal leakage of obligate anaerobes using Fusobacterium nucleatum. In 1997, Chailertvanitkul et al [11] investigated microbial leakage in obturated canals by storing the specimens in artificial saliva and using Streptococcus sanguinis and Prevotella intermedia to test for leakage.…”
Section: Resultsmentioning
confidence: 99%